Components of One-carbon Metabolism Other than Folate and Colorectal Cancer Risk. Issue 6 (November 2016) - Myte, Robin; Gylling, Björn; Schneede, Jörn; Ueland, Per Magne; Häggström, Jenny; Hultdin, Johan; Hallmans, Göran; Johansson, Ingegerd; Palmqvist, Richard; Van Guelpen, Bethany
Abstract : Background: Despite extensive study, the role of folate in colorectal cancer remains unclear. Research has therefore begun to address the role of other elements of the folate-methionine metabolic cycles. This study investigated factors other than folate involved in one-carbon metabolism, i.e., choline, betaine, dimethylglycine, sarcosine, and methionine and relevant polymorphisms, in relation to the risk of colorectal cancer in a population with low intakes and circulating levels of folate. Methods: This was a prospective case–control study of 613 case subjects and 1, 190 matched control subjects nested within the population-based Northern Sweden Health and Disease Study. We estimated odds ratios (OR) by conditional logistic regression, and marginal risk differences with weighted maximum likelihood estimation using incidence data from the study cohort. Results: Higher plasma concentrations of methionine and betaine were associated with modest colorectal cancer risk reductions (OR [95% confidence interval CI] for highest versus lowest tertile: 0.76 [0.57, 0.99] and 0.72 [0.55, 0.94], respectively). Estimated marginal risk differences corresponded to approximately 200 fewer colorectal cancer cases per 100, 000 individuals on average. We observed no clear associations between choline, dimethylglycine, or sarcosine and colorectal cancer risk. The inverse association of methionine was modified by plasma folate concentrations (OR [95% CI] for highest/lowest versus lowest/lowest tertile of plasma methionine/folate concentrations 0.39 [0.24, 0.64], P interaction = 0.06). Conclusions: In this population-based, nested case–control study with a long follow-up time from baseline to diagnosis (median: 8.2 years), higher plasma concentrations of methionine and betaine were associated with lower colorectal cancer risk. See Video Abstract athttp://links.lww.com/EDE/B83 . Abstract : Supplemental Digital Content is available in the text.